Deskripsi Motivasi Belajar Fisika Siswa Kelas X MIPA di SMAN 1 Kota Jambi - Auliya Ramadhanti; Nadia Natalia; Endah Febri; Riska Fitriani (Journal Evaluation in Education (JEE), 2022)
Research objectives: The purpose of this study was to describe the motivation to learn physics in class X MIPA at SMAN 1 Jambi City. Methodology: The data analysis technique used is quantitative analysis using descriptive statistics. The population of this study were students of class X MIPA at SMAN 1 Jambi City. Main findings: The results of this study indicate that the motivation to learn physics in class X MIA at SMAN 1 Jambi City on attitude characteristics is not very good with a score of 25.0 – 45.0 having a percentage of 0%. On the characteristics of bad attitudes with a score of 45.1 - 65.0 have a percentage of 0%, then on the characteristics of quite good with a score of 65.1 - 85.0 have a percentage of 13.9% and on the characteristics of good attitudes with a score of 85.1 - 105 have a percentage of 60.8%, also the last one on the characteristics of attitudes very good with a score of 105.1 – 125 has a percentage of 25.3%. The Novelty of research: This study shows the quality of students in learning physics based on the results of the description of students' motivation in learning physics.